Proceso de atención de enfermería en paciente de 48 años de edad con insuficiencia renal crónica - Barboto Pinela, Jossemar Raúl (2020)
The present case study describes a 48-year-old patient with chronic renal failure. where as a nursing professional, to be able to learn more about this pathology that focuses on the affection of the kidneys which cannot filter the blood in a normal way causing waste to accumulate in your body causing changes in your health. At the time of performing the interventions through the altered functional patterns, I was able to find and realize about his abandonment to his treatment, the reason why he was in a delicate state of health, through the interventions that I chose and executed, I was able to achieve what I wanted and be able to help in the speedy recovery of my patient. The nursing care process is directed to a patient with chronic renal failure, where the nurse, after the assessment, and physical inspection, cephalocaudal, and functional patterns, will be suitable for a nursing diagnosis, where a plan of nursing care, activities and interventions, which will be worked together with medical staff and family members. This medium case study will learn more about chronic renal failure how the damage to the kidneys occurred and also be able to help their relatives through educational talks to be able to provide better moral and emotional support so that they do not abandon their treatment again and follow it as it has been indicated having, as well as a favorable result for your health.